Effects of D-pinitol on diabetes mellitus: an updated review - Pandi, Anandakumar (2023)
The awareness in the consumption of plant-based food has gained attention in the recent years. Phytochemicals are thought to play a critical role in health promotion and in the prevention and management of chronic diseases. These compounds have reported to produce little or no side effects and are thus significantly used in treating various ailments. D-Pinitol is the chief active compound found in soy and soy products. Several studies have shown the health benefits of D-pinitol such as antioxidant, anti-diabetic, anti-inflammatory and anticancer properties. In this review, an attempt has been made to review the effects of D-pinitol against diabetes mellitus in pre-clinical and clinical studies.